The elephant in the room in the Peruvian Civil Code: a necessary approach to the proof of moral damage - Daza Lozada , Carlos Adrián (Revista de Derecho, 2024)
Legal institutions often receive an endogenous treatment that manifests on two levels. On one hand, legal institutions are frequently conceptualized from within the law itself and by legal practitioners, without considering other fields of knowledge that could offer more specific insights into the subject matter. On the other hand, within the legal field, institutions are often developed in isolation: substantive legal institutions are studied without considering the procedural and evidentiary implications that arise from defining them in one way or another. The institution of moral damage in the Peruvian Civil Code is certainly not immune to these issues. This essay, therefore, aims firstly to highlight the unsatisfactory way in which moral damages have been addressed, as the definitions and approaches to this institution have often been disconnected from its evidentiary aspects and its relationship to other sciences, such as psychology. Secondly, it seeks to present several starting points for a more comprehensive conceptualization of moral damages, taking into account evidentiary factors, which are crucial to making this institution effective for compensatory purposes.